Development, longevity, and oviposition of Heliconius charithonia (Lepidoptera: Nymphalidae) on two species of Passiflora - MILLÁN-J., CAROLINA; CHACÓN-C., PATRICIA; CORREDOR, GERMÁN (Revista Colombiana de Entomología, 2010)
The development of Heliconius charithonia on two host plant species was studied at the butterfly house of the Cali Zoo (Colombia) between December 2007 and october 2008. the development of larvae from 90 and 83 eggs laid on Passiflora adenopoda and P. rubra, respectively, was followed. The duration of the five larval instars was measured, as well as pupal weight and length. the emerged adults were marked, measured, sexed and released in the exhibition area of the butterfly house and weekly censuses were conducted to estimate longevity. Larval survival was higher in P. adenopoda (76.4%) than in P. rubra (33.9%). Pupal mortality reached 3% in P. rubra while in P. adenopoda all pupae were viable. the results indicate that P. adenopoda is the host plant most suitable for mass rearing of H. chari- thonia, since on this host species we observed better larval development, larger and heavier pupae, and adults showed greater wing length and greater longevity (140 days vs 70 days). oviposition preferences showed that among all eggs (N = 357), 71% were laid on P. adenopoda even in those cases where females developed on P. rubra.